Challenges surrounding penile prostheses insertion following acute priapism - Tatem, Alex; Kovac, Jason R. (Translational Andrology and Urology, 2017)
The role of immediate penile prosthesis placement in the management of patients suffering from acute priapism is controversial. Multiple temporal and intra-operative factors influence the decision of physicians to offer the option of early penile prosthesis placement. Although the duration of an ischemic priapism episode is the most predictive factor for determining long-term functional outcomes, treatments can range from conservative (observation) to aggressive (penile prosthesis insertion). In either situation, it is important to educate patients that many who present within 24 hours of priapism onset will still likely develop some form of lasting erectile dysfunction (ED) (1).